Parental anxiety to unexplained bruising: a case report of acquired platelet dysfunction with Eosinophilia - Anuar, Muhamad Azamin; Misaridin, Nur Farah Izzati; Md Latip, Muhammad Shafiq Safwan (2022)
Bruising in the form of ecchymosis and purpura in a healthy child, should be taken into serious consideration when it occurs spontaneously with no logical explanation. Baseline blood investigations including blood film are mandatory to rule out malignancy. Thrombocytopenia is very common in pediatric population however platelet dysfunction is a challenging diagnosis that require extensive laboratory investigations. Acquired platelet dysfunction with eosinophilia is a syndrome that requires more awareness among pediatricians especially in Southeast Asia region to avoid parental anxiety. We report a three years old boy with a long history of spontaneous bruising that was eventually treated with anti-helminthic agent. The patient was seen by many clinicians over a period of time but unable to justify parental expectation and relieve their anxiety.